A investigação em literacia informacional: abordagem a partir de um projeto de âmbito nacional - Silva, Armando Malheiro da (2016)
Information literacy (IL) has been establishing itself as an important issue in the field ofInformation Science. When analyzing literature, four main lines of research emerge, namely, theoretical,interface studies relating epistemological aspects and more practical ones and research that study the levelsof information literacy in different age groups. Between 2007 and 2010 a project has been developed -Information literacy in the context of the European Higher Education Area: a study of information competencies in Portugal (elit.pt) that fits in the latter type of research. The aim of the project was tounderstand how High Education students face information skills required by the European HigherEducation Area (EHEA). In this paper the team experience is presented in terms of research methodologyfor analyzing information skills. The research done has had some peculiarities that distinguish it from otherstudies of IL. A theoretical framework has been build and it justified the practical aspects of the project, alarge sample that included various regions of the country was analyzed and either qualitative or quantitativemethods have been used. Thus, the ability and the attitude of students in higher education in relation toinformation literacy has been evaluated but also of the secondary school students as education is a systemand consequently, understanding the skills acquired at this level determine the behavior of subsequentinformation use. As the levels of IL could potentially be dissimilar in different geographic areas of Portugalthe study on a national scale, to allow comparisons between regions with different levels of developmenthas been conducted. Qualitative methods (for interviews and focus group) were firstly used allowingobtaining valuable indicators about the expectations, needs and using of information by students. Theseindicators were later employed in the construction of the questionnaire, which was applied in ten secondaryschools and ten Schools of higher education (university and polytechnic) and that has been statisticallyprocessed. This questionnaire consisted of 54 items with a core group and cross-cutting issues. Thestatistical data treatment has allowed, for example, comparing the results of some groups (gender, secondaryand higher education levels, university and polytechnic degrees and different regions of the country). Thispaper presents the methodological choices of the research and some of its limitations emphasizing theimportance of developing effective methods for research in IL.